Analysis of existing dairy farming in Goa - NAIK, P K; DHURI, R B; SWAIN, B K; KARUNAKARAN, M; CHAKURKAR, E B; SINGH, N P (The Indian Journal of Animal Sciences, 2013)
A study was envisaged to highlight the existing dairy farming practices and to analyze the constraints of the dairyfarming in Goa. A total of 66 farmers were selected randomly from different talukas of Goa, which covered around1,170 dairy animals. Only 8% farmers had dairying as the primary occupation and majority (74%) of the farmers hadagriculture or horticulture as the primary occupation. Based on the number of milch animals 51.5, 27.3, 16.7 and 4.5,per cent farmers were marginal, small, medium and large, respectively. The wet average and herd average were 7.62 kg/ day and 5.79 kg/day. Among the ingredients of the home-made concentrate feeds, ground maize and cotton seed cake were most preferred. Majority of the dairy farmers were using naturally grown karad grasses only during rainy season. Among the un-conventional feeds, spent brewers’ grains were mostly used. It can be concluded that there is need of awareness programmes on scientific feeding practices and interventions are needed in the traditional feeding practices of the dairy animals to make the dairy farming a more profitable venture.